Mikhail Speransky on the Basic Principles of Reorganization of the Higher Public Administration - LUKOVSKAYA, Dzhenevra; SHEVELEVA, Natalya; VOLKOVA, Svetlana; VASILYEV, Ilya; ILYIN, Andrey (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The article is devoted to the project of state reform, developed in 1809 by Prime Minister Mikhail Speransky, which is regarded as the origins of modern Russian constitutionalism. The need for reorganization of public governance system settled archaic existing political system in general, and the state apparatus in particular. The idea of the reform was based on a kind of division of powers under the control of the sovereign. The only element of the reform implemented was the creation of the State Council, which was intended to carry out legislative work and interpretation of laws, as well as provide supervision of the legislature from the executive power. Today, however, the concept of Speransky is being realized in the Russian Federation, including the provision of the free access to information on the activities of public authorities. The Russian Federation carries out the reform of supervisory powers of the public authorities, which allows rethinking the classic public-legal heritage.
Keywords: Speransky, state budget, public administration, state reform